Dolichopus simillimus - Nunes, Rui (2020)
JUSTIFICATION: Dolichopus simillimus is an endemic species of the Azores (Portugal), being present, at least historically, at a single site in Pico island. From the historical data, this species would have a very small Extent of Occurrence (8 km² ) and Area of Occupancy (8 km² ), and it is possible that this species has declined in the past as a result of human activity. The present situation of this species needs to be further assessed, and further research is needed into its population, distribution, threats, ecology and life history. Conservation of native wet and boggy areas and natural streams and other water bodies could potentially aid this species conservation. Based upon the lack of data regarding this species population, distribution, threats and ecology, this species is assessed as Data Deficient (DD).